Microbiological Quality Of Broiler Meat Sold On The Streets Of Fianarantsoa - J. L., Rajaonarision; V. A, Rabemananjara; R., Rakotoarimanana; N. J. A., Ramahatradraibe; A.D., Razafindrazanakolona; R., Randrianarivelo; Rahelivololoniaina B., Robijaona; R. M., Rafanomezantsoa (Budapest International Research in Exact Sciences (BirEx) Journal, 2024)
The aim of this article is to study the microbiological quality of broiler meat sold in the city of Fianarantsoa. A series of observations among producers showed that there are slaughterhouses set up in deplorably hygienic conditions throughout the districts. Microbiological analyses have shown the presence of indicators of faecal contamination accompanied by dangerous germs. All stages of the process, from the slaughterhouse exit to the butcher's stalls and through to the most commonly consumed foods, were studied. All indicators far exceed the recommended health numbers. The accumulation of undesirable and pathogenic microorganisms has been distinguished. Enterobacteria indicative of fecal contamination, particularly fecal coliforms, were particularly noteworthy. In raw meats, laboratory analyses revealed Enterobacter cloacae (1,5. 102 CFU/g to >106CFU/g), Enterococcus sp (104 CFU/g), Escherichia coli (4. 103CFU/g) including E. coli -glucuronidase positive at 2,3.102CFU/g, les Staphylococcus ssp (102CFU/g), St. saprophyticus (2.104CFU/g), St. aureus (≈102/g CFU/g) and small colony visibilities of Salmonella ssp (≈1CFU/g to ≈2CFU/g). In grilled meats, Enterococcus feacalis (102CFU/g), Enterobacter cloaceae (4.102CFU/g) Enterococcus sp (3.102 CFU/g), E. coli (2.103CFU/g), St. saprophyticus (1,5.103CFU/g) and some levures Candida sp (>102CFU/g), were spotted. In fried foods, Enterococcus feacalis (103UFC/g), Enterococcus sp (3.105UFC/g), Escherichia coli (≈106UFC/g), Staphylococcus ssp (103UFC/g) and Candida sp yeasts (>102UFC/g) were identified. As for snacks, atypical forms were discovered by the presence of Enterococcus sp and Streptococcus sp (from 102 to 104UFC/g), E. coli (4.104/g), St. haemoliticus (104 UFC/g), St. aureus (2.102UFC/g) and Candida sp yeasts (>104UFC/g) fied. This article concludes that the sanitary and microbiological quality of broiler meat sold on the streets of Fianarantsoa is very critical, and requires appropriate measures and controls.